PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 31 PADANG - Amalia, Fitri; R., Syahrul; Arief, Ermawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this research is to explain the effect of discovery learning through audiovisual media toward writing skill on exposition text for eight grade of SMP Negeri 31 Padang students. This research used quantitative method which usedone group pretest and posttest design. The population of this research was the eight grade students of SMP Negeri 31 Padang. There was 271 population but there was only one class to be the sample. It was class VIII.1 whivh consisted of 34 students that choosen by using purposive sampling technique. The data of this research was the score of the result of students’ writing skill in exposition text before and after using discovery learning model through audiovisual media. There are three result of this research. First, the students’ writing skill in exposition text before using discovery learning through audivisual media was 68,14. Second, the students’ writing skill in exposition text after using discovery learning through audiovisual media was 82,84. Third, based on the t-test alternative hypotesis (H1) is accepted on the significant degree 95% and degree (dk) = n – 1 tcount > ttable (7,00>1,70).   Kata kunci: discovery learning, media audiovisual, keterampilan menulis, teks eksposisi.